LINGUOPOETIC FEATURES OF OFFENSIVE WORDS IN UZBEK AND ENGLISH LITERARY TEXTS (CAHIERS MAGELLANES-NS, 2024)
Annotation: This article explores the linguopoetic features of offensive words in Uzbek and English literary text, examining how each culture utilizes swearing to convey emotions, societal critiques, and character depth. Through phonetic analysis, symbolism, and cultural context, the article highlights how offensive language in both literary texts reflects societal taboos, power dynamics, and social values. While Uzbek literary text uses offensive words selectively to address issues of honor and family, English literary text often employs profanity to emphasize rebellion and realism, showing how linguistic choices enrich the emotional and cultural impact of literary expression.